Business under threat: the criminal liability of trade secret theft in Malaysia? - Abd. Jalil, Juriah; Hassan, Halyani; Abdul Rahman, Nasarudin; Raja Mohd Ali, Raja Badrol Hisham; Mohamed, Duryana; Najib, Ahmad (Universiti Malaysia Sarawak, 2020)
Maintaining and ensuring secrecy of valuabletradesecret offers competitive advantage to its owner over the competing rival. Because of this, the trade secret is often subject to various threats ranging from misappropriation, theft and corporate espionage launched by rivals and also the employee. Such threats can impede growth of the victimized firms and discourage further innovative and inventive endeavor. One of the ways to deter such offence is by providing specific criminal sanction for the theft of trade secret as practiced in the US and Japan. The US regards theft of trade secrets as a federal crime under the Economic Espionage Act 1996 and in Japan, theft of trade secret is a crime under the Unfair Competition Law. In comparison, Malaysian law does not provide any specific legislation criminalizing theft of trade. But being a member of the TTPA, Malaysia is required to criminalize such theft. This article analyzes the competency of the existing criminal, cyber and national security laws in Malaysia to address the issue. In doing so, the practice of the US and Japan is taken as example to shed light as to the proper implementation of criminal prosecution against the theft of trade secret.